Integrative taxonomy resolves taxonomic uncertainty for freshwater mussels being considered for protection under the U.S. Endangered Species Act. Issue 1 (December 2018) - Johnson, Nathan; Smith, Chase; Pfeiffer, John; Randklev, Charles; Williams, James; Austin, James
Abstract Objectively delimiting species boundaries remains an important challenge in systematics and becomes urgent when unresolved taxonomy complicates conservation and recovery efforts. We examined species boundaries in the imperiled freshwater mussel genusCyclonaias (Bivalvia: Unionidae) using morphometrics, molecular phylogenetics, and multispecies coalescent models to help guide pending conservation assessments and legislative decisions. Congruence across multiple lines of evidence indicated that current taxonomy overestimates diversity in theC. pustulosa species complex. The only genetically and morphologically diagnosable species in theC. pustulosa species complex wereC. pustulosa andC. succissa and we considerC. aurea, C. houstonensis, C. mortoni, andC. refulgens to be synonyms ofC. pustulosa . In contrast, all three species in theC. nodulata complex (C. necki, C. nodulata, andC. petrina ) were genetically, geographically, and morphologically diagnosable. Our findings have important conservation and management implications, as three nominal species (C. aurea, C. houstonensis, andC. petrina ) are being considered for protection under the Endangered Species Act.